Pelaksanaan Bimbingan Pranikah Dalam Mempersiapkan Calon Pengantin Di Kantor Urusan Agama (KUA) Kecamatan Sukamakmur - Aja Munika; Mahdi; Mira Fauziah (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2026)
This study was motivated by the limited understanding of prospective brides and grooms regarding married life, which may potentially lead to conflicts after marriage. The purpose of this study was to describe the implementation of premarital counseling in preparing prospective couples for marriage at the Office of Religious Affairs (KUA) of Sukamakmur District. This study employed a qualitative approach with a descriptive method. Data were collected through interviews and documentation involving five informants, consisting of KUA officials, a marriage registrar, Islamic religious counselors, premarital counseling facilitators, and prospective brides and grooms. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that premarital counseling at the KUA of Sukamakmur District was conducted through the Marriage Guidance Program (BIMWIN), covering topics such as the rights and obligations of husbands and wives, family communication, household financial management, family health, and conflict resolution. The implementation of premarital counseling contributed to improving prospective couples’ understanding of married life. This increased understanding was reflected in their readiness to perform their respective roles and responsibilities, establish effective communication with their partners, and deal with family problems more wisely. Therefore, premarital counseling contributes to preparing prospective couples in terms of knowledge, mental readiness, and emotional preparedness before entering married life. Keywords: Premarital Counseling, Prospective Brides and Grooms, KUA.